Factors Related to the Application of Perianesthesia Education in Indonesia - Putu Atika Parwati; Sang Ketut Arta; Luh Gde Nita Sriwahyuningsih (PROMOTOR, 2023)
Health education or perianesthesia health education for patients who will perform anesthesia is very important to provide information on how they should prepare before and after the anesthesia procedure. Perianesthesia health education contains matters related to anesthesia actions from pre, intra, to post-anesthesia and will affect patient readiness in facing post-anesthesia conditions. Perianesthesia health education has not been carried out optimally due to various factors. The purpose of this study was to determine the factors associated with the provision of perianesthesia education in Indonesia. The design of this study was cross-sectional. The population taken is anesthesiologists throughout Indonesia. The data analysis used is a multivariate binary logistic regression test. The results of the analysis found that most anesthesiologists had a high implementation of perianesthesia education (59.8%). Interpersonal relationships (adj. OR: 2.81) and social support (adj. OR: 2.30) were significantly associated with perianesthesia education. Further research still needs to be done with longitudinal research methods or in the long term and continuously can be done so that the results of the study are always by changes that may occur.